PERANCANGAN ALAT BANTU MANDI DAN AKTIFITAS TOILET PORTABEL TUNADAKSA BAGIAN BAWAH DENGAN MENGINTEGRASIKAN TAHAPAN FRONT-END PROCESS DAN METODE TRIZ - Patrisius Edi Prasetyo; Agustinus Eko Susetyo; Dyah Ari Susanti (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2021)
Physical disability supporting facilities to help the independence of their activities. This study designed a tool for bathing and lower physical disability toilets to carry out these activities without the help of other people. A similar design was carried out in previous studies that had not accommodated public bathroom activities outside the home while traveling. Previously designed dimensions did not allow carrying to traveling and only accommodated the type of toilet seat. Based on these shortcomings, this study designed a portable bathing and toilet activity aid so that the lower quadriplegic can be used while traveling practically and accommodating the sitting and squat toilets. The product of the design result is expected to support the independence of the quadriplegic to carry out activities outside the home to expand their accessibility. The design process of this product is carried out with the Front-end Processstage method as the main design method and integrated with the TRIZ method to help resolve contradictions in the design process while determining specifications and targets and the process of selecting the concept of a work product system. This research produces a 3D modeldesign and technical specifications of the product.